Korelasi Kadar HbA1c Dengan Kadar Kreatinin Pada Pasien Diabetes Melitus Kronis - Frederikus Ahat (Universitas Muhammadiyah Surabaya, 2023)
Uncontrolled diabetes mellitus will lead to various chronic complications, both microvascular and macrovascular complications. HbA1c examination is effective for long-term monitoring of blood glucose for people with diabetes mellitus. A high HbA1c value is used as a measure of the development of complications of diabetes mellitus. Diabetic nephropathy is the most common complication of diabetes mellitus which can end in kidney failure resulting in damage to the glomeruli. Indications to determine kidney function impairment is creatinine examination. This study aims to determine the correlation between HbA1c levels and creatinine levels in patients with chronic diabetes mellitus at the Clinical Pathology Laboratory of the Bajawa Regional General Hospital. Analytical observational research with an approach cros- sectional using techniques purposive sampling 35 chronic DM patients. Test results who squares shows that the value of p = (0.687) > α (0.05), thus it can be concluded that there is no relationship between HbA1c levels and Creatinine levels in patients with chronic diabetes mellitus. Keywords: HbA1c, Creatinine, Diabetes Mellitus.